PENGARUH PENGUNYAHAN PERMEN KARET YANG MENGANDUNG XYLITOL TERHADAP PENURUNAN INDEKS PLAK PADA PEROKOK - Popy Sandra; Yustini Allioes; Susi Susi (Faculty of Dentistry Universitas Andalas, 2015)
Dental plaque plays main important role in cause of caries and periodontal disease. The one of control is to chewing gum containing xylitol. The aim of the study was to evaluate the effect of chewing gum containing xylitol in reducing the plaque index scores in smoker. The method of this study was quasi experiment with pretest-posttest design involved smoker sample total 35 people. Examination plaque index score was conducted over 2 days using PHP-M plaque index. Data analysis is conducted using Paired t-test. Average plaque index prior to chewing gum containing xylitol is 37,9714±8,62106 and average plaque index after to chewing gum containing xylitol is15,2000±4,96340. After chewing, it shows that mean percentage plaque index prior and after is 22,77143±9,49330 with p<0,05. So, chewing gum containing xylitol are equally effective reducing the plaque index scores in smoker. Keywords : Chewing gum containing xylitol, plaque index, smoker.